(untitled) (Conferencea, 2024)
This article describes the means and methods of developing students’ logical thinking skills in the process of learning their native language. In particular, it is argued that the main tools are mobile applications, virtual libraries and native language textbooks. The possibilities of using methods such as anogram, pictogram, and five-minute essay in the process of teaching a native language are also highlighted.